Editorial - Miranda, Diego (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
The object of study of the Horticultural Sciences is focused on the technical improvement of horticultural production systems, in topics such as cultivar evaluation, propagation methods, irrigation, nutrition, phytosanitary management and post-harvest techniques, both in open field crops, as in protected environments, which are part of the contents of our Colombian Journal of Horticultural Sciences (RCCH).